2011
DOI: 10.1007/s00405-010-1454-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glass ionomer cement and incus interposition in reconstruction of incus long process defects

Abstract: The ossicles may be affected through the mass effect of the pathological tissue in chronic otitis media. Ossicular reconstruction may be accomplished using the patients' own ossicles or with alloplastic materials. Glass ionomer ossiculoplasty is a fast, efficient, safe and cost-effective method and it has been used more frequently in recent years. Forty-six patients who had surgery for chronic otitis media were included in this study. All patients had an incus long process defect and a normal stapes superstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
0
22
2
5
Order By: Relevance
“…Unfortunately, long-term mean ABG (at 12 months) in our incus interposition control group (23.1 dB) was not as favourable as results reported by other authors, such as Dere et al [18] (20 dB), Emir et al [19] (20.4 dB) and O'Reilly et al (18.6 dB) [11].…”
Section: Discussioncontrasting
confidence: 80%
“…Unfortunately, long-term mean ABG (at 12 months) in our incus interposition control group (23.1 dB) was not as favourable as results reported by other authors, such as Dere et al [18] (20 dB), Emir et al [19] (20.4 dB) and O'Reilly et al (18.6 dB) [11].…”
Section: Discussioncontrasting
confidence: 80%
“…In some previous studies, the glass ionomer cement and incus interposition were also compared. Dere et al (23) found that the use of bone cement and incus interposition resulted in similar significant hearing results (i.e., ABG gain of 6.3 and 8.5 dB, respectively). In their study where the efficacy of incus interposition, PORP, and bone cement in isolated incudostapedial disarticulation was compared, Babu and Seidman (7) showed significant postoperative hearing improvements in all cases.…”
Section: Discussionmentioning
confidence: 89%
“…La comparaison du ciment osseux ionomérique avec les autres matériaux d'ossiculoplasties partielles a été également faite et conclue à sa non-infériorité, notamment sur les transpositions d'enclume [2,23] ou les prothèses en titane [20], avec des résultats audiométriques au moins équivalents. Cependant, la neurotoxicité connue de l'aluminium (composant en partie le ciment ionomé-rique) [7] et des cas d'encéphalopathie aluminique, allant jusqu'au décès des patients [8,24], secondaires à son utilisation ont été décrits dans la littérature ; et même si d'autres études ont montré une bonne tolérance à long terme [9], ces risques sont à prendre en considération dans le choix du matériau de reconstruction ossiculaire.…”
Section: Discussionunclassified